Lake of the Ozarks : my surreal summers in a vanishing America - Geist, William (New York : Grand Central Publishing, 2019)
"Bill Geist reflects on his coming of age in the American heartland of the Midwest and traces his evolution as a man and a writer, in the summers between high school and college, before he went off to Vietnam and the country went to Hell."--Provided by publisher
HB
Keywords: Geist, William -- Childhood and youth; Summer resorts -- MIssouri -- Ozarks, Lake of the, Region -- Anecdotes; Teenage boys -- Missouri -- Biography; Teenagers -- Missouri -- Social life and customs -- 20th century; Summer employment -- Missouri -- Anecdotes; Youth -- Employment -- Missouri -- Anecdotes; Coming of age; Ozarks, Lake of the, Region (Mo.) -- Social life and customs -- 20th century; Missouri -- Social life and customs -- 20th century -- Anecdotes